Deltoid Compartment Syndrome following Serratus Anterior free flap reconstruction. Issue 2 (1st December 2016) - Farrell, Eric; Tevlin, Ruth; O'Broin, Eoin
Summary: Compartment syndrome is a well‐described process resulting from increased pressure in an osseo‐fascial space, most commonly involving the lower extremity. Here we describe the rare occurrence of deltoid compartment syndrome occurring in a 42‐year‐old male with a heavy muscular build, that occurred following a serratus anterior free flap reconstruction. Few cases of deltoid compartment syndrome have been described. A lateral decubitus positioning for the operation, despite liberal use of padding and support, may have contributed to its development. Acknowledgement of risk factors (which include elevated BMI, large muscle mass, history of anabolic steroid usage) should alert the clinician to be vigilant and check regularly for symptoms and signs in order to ensure early recognition and management.